Hybrid Energy Harvesting Low Energy Adaptive Clustering Hierarchy (HEH-LEACH) - Chaudhari Monali, Bhaskar A.A (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Network (WSN) plays a noteworthy role in many industrial, automation, and surveillance applications. Network lifetime is a critical issue in the WSN which directly depends upon the battery life of the sensor node. To cope up with this problem hybrid energy harvesting low energy adaptive clustering hierarchy (HEH- LEACH) is proposed which efficiently uses the solar energy and wind energy for the charging of the battery in a WSN node based on the environment condition and the hybrid solar- wind operated sensor nodes are placed in the sub-region containing a maximum number of nodes. The performance of the system or network is evaluated based on network lifespan and battery consumption. It shows a considerable increase in the performance of the proposed method over the other variants of LEACH based on the single harvestingsource. Keywords: Wireless Sensor Network, Hybrid Energy Harvesting–LEACH, Solar-wind operated nodes, Network lifetime, Battery consumption.